HIV Preexposure Prophylaxis Service Delivery Models for Emergency Departments: A Qualitative Study - Ethan Cowan MD, MS; Susie Hoffman DrPH; Laurie J Bauman PhD; Yvette Calderon MD, MS; Tatiana Gonzalez-Argoti BS; Christine T Rael PhD; Jonathan Porter MPH; Joanne E Mantell MS, MSPH, PhD (Journal of the International Association of Providers of AIDS Care)
Background Oral preexposure prophylaxis (PrEP) effectively prevents HIV but is underutilized in the United States, particularly among populations with higher incidence of HIV. Emergency departments (EDs), which often care for medically underserved individuals, could play a key role in expanding PrEP access. However, integrating PrEP into ED workflows presents challenges. Methods This qualitative study involved interviews with 22 stakeholders from 15 EDs and 4 sexual health clinics across the United States. Participants included ED leaders, providers, and navigators. The data were analyzed using a PrEP care cascade model, focusing on provider buy-in, patient identification, education, PrEP initiation, and linkage to care. Results Key barriers included limited provider knowledge, ED priorities focused on acute care, and the reliance on grant funding without long-term plans for sustainability. Successful programs relied on ED champions to advocate for PrEP and improve staff engagement. Some EDs offered same-day PrEP prescriptions or starter packs, which improved uptake, but most relied on referrals and had low follow-up rates. Patient identification strategies, such as using navigators or risk scores, varied across sites. Education was often led by ancillary staff, as ED providers had limited time and training. Sustainability remained a major challenge, as most programs were dependent on short-term funding. Conclusions To expand PrEP access in EDs, it is essential to address systemic barriers, improve provider training and establish sustainable funding models. Streamlined workflows, dedicated staff, and targeted interventions can help EDs play a more active role in HIV prevention.